Risk assessment heuristics: Cues and intention to use a condom in casual sex. (April 2017) - Rinaldi-Miles, Anna; Quick, Brian L; McCloskey, Laura
Objective: This study examined the relationship between three heuristic cues (consistency, liking and social proof) and condom use in casual sex relationships utilising the theory of planned behaviour. Participants: Totally, 388 US college students were surveyed. Method: Three vignettes for each cue primed students to project their willingness to use a condom during casual sex encounters. Results: Repeated-measures multivariate analysis of covariance (MANCOVA) revealed that the cues exerted significant main effects on attitude ( F (5, 1, 935) = 6.16, p < .001), subjective norms ( F (5, 1, 930) = 5.626, p < .001), perceived behavioural control ( F (5, 1, 935) = 8.51, p < .001) and behavioural intentions ( F (5, 1, 930) = 2.44, p = .033). Post hoc analysis revealed condom avoidance behavioural intentions were more likely for the vignette depicting social proof ( M = −1.26, standard deviation [ SD ] = 1.08). Conclusion: Findings indicate that heuristic cues influence college students' condom use intentions, and prevention programmes should incorporate cues to increase effectiveness.